Impact of Alzheimer's disease and related dementia diagnosis following treatment for bladder cancer. Issue 7 (September 2020) - Jazzar, Usama; Shan, Yong; Klaassen, Zachary; Freedland, Stephen J.; Kamat, Ashish M.; Raji, Mukaila A.; Masel, Todd; Tyler, Douglas S.; Baillargeon, Jacques; Kuo, Yong-Fang; Mehta, Hemalkumar B.; Bergerot, Cristiane D.; et al.
Abstract: Objectives: Our objective was to assess the incidence of Alzheimer's Disease and related dementia diagnosis following treatment for muscle-invasive bladder cancer and impact on survival outcomes. Materials and Methods: A total of 4814 patients diagnosed with clinical stage T2-T4a, N0, M0 bladder cancer between January 1, 2002 to December 31, 2011 using the Surveillance, Epidemiology, and End Results (SEER)-Medicare database were identified. Alzheimer's disease and related dementia diagnosis was identified using International Statistical Classification of Disease-Ninth Edition outpatient and inpatient codes. Incidence of dementia following treatment were calculated and reported as dementia cases per 10, 000 person-years. Cox proportional hazards models were used to assess the impact of dementia on survival outcomes. Results: Of the 4814 patients, 2403 (49.9%) underwent radical cystectomy (RC) and 2411 (50.1%) underwent radiotherapy (RTX) and/or chemotherapy (CTX). Overall, 837 (17.4%) patients developed Alzheimer's disease and related dementia following bladder cancer treatment. There was no significant difference in the incidence of Alzheimer's disease and related dementia following either treatment. Patients diagnosed with Alzheimer's disease and related dementia had worse overall (Hazard Ratio (HR), 2.64; 95% Confidence Interval (CI), 2.41–2.89) and cancer-specific (HR, 2.45; 95% CI, 2.18–2.76) survival than those without a dementia diagnosis following treatment. Conclusion: While we observed no difference in new-onset Alzheimer's disease and related dementia diagnosis following RC or RTX and/or CTX, patients with a Alzheimer's and related dementia diagnosis was associated with worse overall and cancer-specific survival. These findings have important implications for screening and the development of targeted interventions for improving outcomes in older adults following complex cancer treatments, as observed in this bladder cancer population.